Recognising out-of-hospital cardiac arrest during emergency calls increases bystander cardiopulmonary resuscitation and survival. (June 2017) - Viereck, Søren; Møller, Thea Palsgaard; Ersbøll, Annette Kjær; Bækgaard, Josefine Stokholm; Claesson, Andreas; Hollenberg, Jacob; Folke, Fredrik; Lippert, Freddy K.
Abstract: Background: Initiation of early bystander cardiopulmonary resuscitation (CPR) depends on bystanders' or medical dispatchers' recognition of out-of-hospital cardiac arrest (OHCA). The primary aim of our study was to investigate if OHCA recognition during the emergency call was associated with bystander CPR, return of spontaneous circulation (ROSC), and 30-day survival. Our secondary aim was to identify patient-, setting-, and dispatcher-related predictors of OHCA recognition. Methods: We performed an observational study of all OHCA patients' emergency calls in the Capital Region of Denmark from 01/01/2013–31/12/2013. OHCAs were collected from the Danish Cardiac Arrest Registry and the Mobile Critical Care Unit database. Emergency call recordings were identified and evaluated. Multivariable logistic regression analyses were applied to all OHCAs and witnessed OHCAs only to analyse the association between OHCA recognition and bystander CPR, ROSC, and 30-day survival. Univariable logistic regression analyses were applied to identify predictors of OHCA recognition. Results: We included 779 emergency calls in the analyses. During the emergency calls, 70.1% (n = 534) of OHCAs were recognised; OHCA recognition was positively associated with bystander CPR (odds ratio [OR] = 7.84, 95% confidence interval [CI]: 5.10–12.05) in all OHCAs; and ROSC (OR = 1.86, 95% CI: 1.13–3.06) and 30-day survival (OR = 2.80, 95% CI: 1.58–4.96) in witnessed OHCA. Predictors of OHCA recognition were addressing breathing (OR = 1.76, 95% CI: 1.17–2.66) and callers located by the patient's side (OR = 2.16, 95% CI: 1.46–3.19). Conclusions: Recognition of OHCA during emergency calls was positively associated with the provision of bystander CPR, ROSC, and 30-day survival in witnessed OHCA.